(untitled) (Nordic Journal of Practical Theology, 2024)
The number of funerals conducted under the auspices of the Church of Sweden, as well as the attendance at Church of Sweden funerals, has steadily declined since the turn of the millennium, including among members of the Church of Sweden. Drawing on current statistics and interviews with parish staff and funeral directors, this article highlights these changes and discusses the following aspects which we argue are crucial: the opportunity for individual customization of funeral services and the relationship to the Church of Sweden. Insights from four parishes/dioceses reveal both similarities and differences, emphasizing the geographical context’s influence on funeral customs. The post-secular condition presents both opportunities and challenges for traditional religious institutions such as the Church of Sweden to navigate.